Vitamin D and its implication in neurofibromyalgia - Khatri, R; KC, Sanjay; Shrestha, P; Sinha, JN (Sunsari Technical College Journal, 2013)
New and emerging roles of Vitamin D are being uncovered, except for its known traditional roles in Bone mineralisation and Calcium metabolism. Evidences associating it with cell proliferation and multiplication have linked with its potential role in cancer causation and treatment modality. Vitamin D is also finding its importance in mental disorders, proper immune functioning, and cognitive performances. Here we present a review article on association of Vitamin D with common but infrequently diagnosed cases non specific musculoskeletal pain, Neurofibromyalgia. DOI: http://dx.doi.org/10.3126/stcj.v1i1.7987 Sunsari Technical College Journal Vol.1(1) 2012 45-47